The folly of the cross: the passion of Christ in theology and the arts - early modernity - Viladesau, Richard (Oxford University Press, 2018)
The Folly of the Cross' is the fourth book in Richard Viladesau's series examining the aesthetics and theology of the cross through Christian history. Previous volumes have brought the story up through the Baroque era. This new book examines the reception of the message of the cross from the European Enlightenment to the turn of the twentieth century